2014
DOI: 10.1016/j.rmed.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Observational study in severe asthmatic patients after discontinuation of omalizumab for good asthma control

Abstract: The discontinuation of omalizumab was not associated with any rebound effect or exacerbation of the disease, and control was sustained throughout the follow-up period of at least 6 months in nearly half of all patients, including all of those who had been treated for 3.5 years or more. After the reintroduction of omalizumab, 4 out of 20 patients did not respond again.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 17 publications
4
64
1
5
Order By: Relevance
“…Treatment with omalizumab has been associated with a reduction or discontinuation of added on oral corticosteroid required for controlling asthma. 11,12,24 In our study, omalizumab treatment was also associated with a trend toward a reduction in the dose of inhaled corticosteroid, although this trend did not reach statistical significance. In a much larger prospective observational cohort study of moderate-to-severe allergic asthma, omalizumab therapy was associated with a reduction in doses of ICS, SABA, and leukotriene modifiers over 2 years in a "real-world" setting.…”
Section: Treatment Discontinuation and Restart Of Omalizumab Treatmentcontrasting
confidence: 73%
See 1 more Smart Citation
“…Treatment with omalizumab has been associated with a reduction or discontinuation of added on oral corticosteroid required for controlling asthma. 11,12,24 In our study, omalizumab treatment was also associated with a trend toward a reduction in the dose of inhaled corticosteroid, although this trend did not reach statistical significance. In a much larger prospective observational cohort study of moderate-to-severe allergic asthma, omalizumab therapy was associated with a reduction in doses of ICS, SABA, and leukotriene modifiers over 2 years in a "real-world" setting.…”
Section: Treatment Discontinuation and Restart Of Omalizumab Treatmentcontrasting
confidence: 73%
“…24 Outcomes of asthma control can be measured by assessment of current symptom scores, frequency of asthma exacerbations and oral corticosteroid usage. 25 We found that a composite symptom score of asthma control, the asthma control test (ACT) score, was significantly improved at the 16 th week of treatment in this study.…”
Section: Treatment Discontinuation and Restart Of Omalizumab Treatmentmentioning
confidence: 99%
“…Although the exact underlying mechanisms of airway remodelling still elude us, the existence of chronic persistent inflammation, involving longstanding exposure of the airways to a variety of environmental agents, cells and mediators, is generally considered a prerequisite [7][8][9], and IgE is central to the initiation and persistence of this inflammation [2,10]. Therapeutic agents with the potential to block the allergic cascade at an early stage, such as omalizumab, may potentially also attenuate airway remodelling, a possibility also supported by evidence suggesting that long-term anti-IgE treatment remains effective long after it has been discontinued [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Эти пациенты полу-чают преимущественно комбинированную терапию -высокие дозы ингаляционных глюкокортикостероидов и длительно действующие β2-агонисты (ДДБА), а также антагонисты лейкотриеновых рецепторов (монтелукаст), М-холинолитики (тиотропия бромид), пролонгирован-ные ксантины (теофиллин длительного действия) и ген-но-инженерные биологические препараты (монокло-нальные антитела: например, к IgE или IL5). Несмотря на хорошо согласованные и выверенные клинические рекомендации, ряд пациентов с тяжелой астмой не контролируют свою болезнь и продолжают получать системные стероиды, испытывать дневные и ночные симптомы, частые обострения, требующие госпитализа-ции и оказания медицинской помощи в условиях отделе-ния реанимации и интенсивной терапии, отмечают низ-кое качество жизни и существенно ограничены в своей повседневной активности [11,12].…”
Section: Discussionunclassified